Implementing infection prevention practices across European hospitals: an in-depth qualitative assessment. Issue 10 (27th June 2018) - Clack, Lauren; Zingg, Walter; Saint, Sanjay; Casillas, Alejandra; Touveneau, Sylvie; da Liberdade Jantarada, Fabricio; Willi, Ursina; van der Kooi, Tjallie; Damschroder, Laura J; Forman, Jane H; Harrod, Molly; Krein, Sarah; et al.
Abstract : Objective: The Prevention of Hospital Infections by Intervention and Training (PROHIBIT) project included a cluster-randomised, stepped wedge, controlled study to evaluate multiple strategies to prevent catheter-related bloodstream infection. We report an in-depth investigation of the main barriers, facilitators and contextual factors relevant to successfully implementing these strategies in European acute care hospitals. Methods: Qualitative comparative case study in 6 of the 14 European PROHIBIT hospitals. Data were collected through interviews with key stakeholders and ethnographic observations conducted during 2-day site visits, before and 1 year into the PROHIBIT intervention. Qualitative measures of implementation success included intervention fidelity, adaptation to local context and satisfaction with the intervention programme. Results: Three meta-themes emerged related to implementation success: 'implementation agendas', 'resources' and 'boundary-spanning'. Hospitals established unique implementation agendas that, while not always aligned with the project goals, shaped subsequent actions. Successful implementation required having sufficient human and material resources and dedicated change agents who helped make the intervention an institutional priority. The salary provided for a dedicated study nurse was a key facilitator. Personal commitment of influential individuals and boundary spanners helped overcome resource restrictions and intrainstitutional segregation. Conclusion: This qualitative study revealed patterns across cases that were associated with successful implementation. Consideration of the intervention–context relation was indispensable to understanding the observed outcomes.